2014
DOI: 10.1007/s11605-014-2550-0
|View full text |Cite
|
Sign up to set email alerts
|

Child-Pugh A Hepatitis B-Related Cirrhotic Patients with a Single Hepatocellular Carcinoma Up to 5 cm: Liver Transplantation vs. Resection

Abstract: Although more recurrences were observed in Child A cirrhotic patients with a single HCC up to 5 cm after liver resection, liver resection offers a similar 5-year survival to liver transplantation, even for patients with portal hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Our previous study reported that HR of patients with intermediate- and advanced-stage HCC and PHT gave better survival than transarterial chemoembolization [4] , and another study reported that HR was associated with longer survival and time to recurrence than radiofrequency ablation [31] . For Child-Pugh A cirrhotic patients with a single HCC up to 5 cm, HR offers a similar 5-year OS to liver transplantation, even for patients with PHT [32] , [33] . However, the liver donation is shortage in most countries.…”
Section: Discussionmentioning
confidence: 98%
“…Our previous study reported that HR of patients with intermediate- and advanced-stage HCC and PHT gave better survival than transarterial chemoembolization [4] , and another study reported that HR was associated with longer survival and time to recurrence than radiofrequency ablation [31] . For Child-Pugh A cirrhotic patients with a single HCC up to 5 cm, HR offers a similar 5-year OS to liver transplantation, even for patients with PHT [32] , [33] . However, the liver donation is shortage in most countries.…”
Section: Discussionmentioning
confidence: 98%
“…87,88 While 10-year overall survival is better with LT for resectable HCC, 89 many studies have shown similar 5-year overall survival for resection compared to LT in patients with a single <3 cm HCC. 89,90 Patients with a single <3 cm HCC have improved outcome compared to those with larger tumor burden regardless of resection versus LT. [91][92][93] More recently, a large multinational study 94 reported a ~40% cure rate with resection (compared to 75% with LT) in patients with single <3 cm HCC and MELD <11 with similar intention-to-treat survival given the expected 10%-20% waitlist dropout rate in those awaiting LT.…”
Section: Management Of Single Small Hcc Liver Transplantation Versusmentioning
confidence: 99%
“…There was 73 (34.9%) HCC patients undergoing LDLT. Many studies including our previous study demenstrated there was no statistically difference between the HCC patients after DCD and LDLT [28,29].…”
Section: Discussionmentioning
confidence: 88%